Phytochemical composition and bioactivities of lupin: A review - Khan, M.; Karnpanit, W.; Nasar-Abbas, S.; Huma, Z.; Jayasena, Vijay (Blackwell Publishing Ltd, 2015)
Lupin is a nonstarchy grain legume with high protein, dietary fibre and low fat contents. The industrial shift of lupin seed utilisation from feed to food has recently increased the scientific interest to explore its phytochemical composition and biological activities. Lupin seeds contain significant amounts of polyphenols, carotenoids, phytosterols, tocopherols, alkaloids and peptides with antioxidant, antimicrobial, anticarcinogenic and anti-inflammatory activities. Among polyphenols, genistein and their derivatives (isoflavones) are of great importance because of their phytoestrogenic potential. This comprehensive review will help out the readers in understanding the phytochemicals present in lupin and their benefits.